2016
DOI: 10.1111/jfq.12194
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics and Antioxidant Properties of Muffins Enriched with Date Fruit (Phoenix Dactylifera L.) Fiber Concentrates

Abstract: 16Secondary varieties of date from Tunisia are underutilized due to their low commercial 17 quality. Fiber concentrates (DFC) can be obtained from these fruits after a steam pre-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…This may be due to the fat and the fibre present in the seasoning, which affected the structure of the dough, having a negative influence on CO 2 retention [28]. Similar results were obtained when date fruit were incorporated to muffins [29]. Regarding the percentage of weight loss (Table 3), a similar effect was observed in the muffins with a 20% of the product, leading to comparable results to those found by Bender et al [25] when adding products obtained from red and white grape-skins in the elaboration of muffins.…”
Section: Resultsmentioning
confidence: 73%
“…This may be due to the fat and the fibre present in the seasoning, which affected the structure of the dough, having a negative influence on CO 2 retention [28]. Similar results were obtained when date fruit were incorporated to muffins [29]. Regarding the percentage of weight loss (Table 3), a similar effect was observed in the muffins with a 20% of the product, leading to comparable results to those found by Bender et al [25] when adding products obtained from red and white grape-skins in the elaboration of muffins.…”
Section: Resultsmentioning
confidence: 73%
“…The desirable properties and stable emulsion-based food products can be developed by incorporating DF in various food products. Mrabet et al, [35] attempted to extract and analyze dietary fiber from Tunisian secondary date fruit varieties and reported that the content of dietary fiber ranged between 4.7 and 7 g/100 g, thus giving strong indication that the date DF can be utilized as additives in fiber-enriched food [36]. Furthermore, the dietary fiber is well-known for absorption of cholesterol and declines its availability to the human body and thus renders many health benefits including preventing cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Crust and crumb lightness (L* value) of rice muffins were significantly (P < 0.05) higher than MP-and CPenriched muffins (Table 3). The darker colour in MPand CP-enriched muffin is probably due to Maillard reactions caused by proteins, sugars and phenols at a high baking temperature (Mrabet et al, 2016). Additionally, the presence of carotenoid pigment has been reported to darken and increase redness colour of baked muffins (Nath et al, 2018).…”
Section: Quality Characteristics Of Muffinsmentioning
confidence: 99%